The translation of foreign words in an English novel into Malay - Haslina Haroon,; Nurul Syafiqah Daud, (Penerbit Universiti Kebangsaan Malaysia, 2017)
One aspect of language appropriation is the inclusion of foreign words in an English text with the aim of highlighting certain aspects of a culture. This results in a text in which the dominant language, English, is interspersed with foreign words. In the context of translation studies, this phenomenon raises the question of how these foreign words are dealt with when the text is translated. This paper aims to examine this issue by analysing the translation into Malay of foreign words in the English novel by Khaled Hosseini entitled A Thousand Splendid Suns. More specifically, the aim is to determine the translation procedures and the translation strategy used. Foreign words in the English text are first identified and then mapped to their translations in the Malay text. Using Pedersens (2011) taxonomy of strategies in rendering cultural references, the word pairs are analysed in order to determine the translation procedures used. The analysis reveals a total of 174 foreign words in Hosseinis English novel. The mapping of these foreign words to their target language equivalents shows that the procedure used most frequently is retention. In addition, the procedures of retention and specification make up approximately 70 per cent of the procedures used. This in turn points to the adoption of a source-oriented strategy in translating the text. The findings suggest that the translator places priority on faithfulness to the source text; however, measures are also taken by the translator to ensure the comprehensibility of the translation for the target readers.